2019
DOI: 10.1096/fj.201900831r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture of bacterial amyloids in Bacillus biofilms

Abstract: The formation of biofilms provides structural and adaptive bacterial response to the environment. In Bacillus species, the biofilm extracellular matrix is composed of exopolysaccharides, hydrophobins, and several functional amyloid proteins. We report, using multiscale approaches such as solid‐state NMR (SSNMR), electron microscopy, X‐ray diffraction, dynamic light scattering, attenuated total reflection Fourier transform infrared (FTIR), and immune‐gold labeling, the molecular architecture of B. subtilis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(107 citation statements)
references
References 58 publications
7
97
2
Order By: Relevance
“…subtilis depends on the protein TapA, which has a role in promoting TasA stability and fibre formation in vivo (Branda et al, 2006;Romero et al, 2010;Romero et al, 2014;Abbasi et al, 2019;El Mammeri et al, 2019 Figure 3f) and recent NMR analysis has suggested that the C-terminus of TapA is a disordered protein, while the N-terminus is a structured domain, with the two domains interacting with lipid vesicles in a co-operative manner (Abbasi et al, 2019). Collectively, our immunoblot and genetic data support the conclusion that TapA is cleaved at two positions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…subtilis depends on the protein TapA, which has a role in promoting TasA stability and fibre formation in vivo (Branda et al, 2006;Romero et al, 2010;Romero et al, 2014;Abbasi et al, 2019;El Mammeri et al, 2019 Figure 3f) and recent NMR analysis has suggested that the C-terminus of TapA is a disordered protein, while the N-terminus is a structured domain, with the two domains interacting with lipid vesicles in a co-operative manner (Abbasi et al, 2019). Collectively, our immunoblot and genetic data support the conclusion that TapA is cleaved at two positions.…”
Section: Discussionsupporting
confidence: 85%
“…Secondary structure analysis revealed TapA to be a two‐domain protein with significant regions of disorder (Abbasi et al ., 2019). Additionally TapA has recently been shown to form fibres (El Mammeri et al ., 2019). The absence of TapA is correlated with a reduction in the level of TasA in the biofilm matrix (Romero et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Two proteins are affected in the comparison of WT+/− spores ( Supplementary Figure S2A ). YhzC, a functionally unknown protein, is downregulated, and TasA, the major component of biofilm matrix [ 20 ], is upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic interactions and salt bridges can also be important stabilizing interactions for pathogenic amyloid fibrils, as indicated by structural studies of amyloid-β 50,54,61,62 and αsynuclein 51,63 fibrils, as well as for functional amyloids [64][65][66] . The absence of charged amino acid side chains and the absence of purely hydrophobic residues other than Pro within the FUS-LC-C fibril core implies that hydrophobic interactions and salt bridges do not account for the formation of FUS-LC-C fibrils.…”
Section: Comparison Of Fus-lc-c and Fus-lc-n Fibril Structuresmentioning
confidence: 99%